PENGARUH CURRENT RATIO, WORKING CAPITAL TURNOVER, DEBT TO EQUITY RATIO, DAN TOTAL ASSETS TURNOVER TERHADAP RETURN ON INVESTMENT PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Christina, Christina; Monica, Monica; Aurelia, Agnes; Fitria, Sherley; Lina, Lina; Panggabean, Maya Sabirina (Universitas Sam Ratulangi, 2019)
The purpose of this research is to provide and increase knowledge for the readers and to analyze the effect of Current Ratio, Working Capital Turnover, Debt to Equity Ratio, and Total Assets Turnover on Return on Investment in food and beverage companies listed on the Indonesia Stock Exchange for the period 2012-2017. The study population used was 20, the research sample of 11 companies. The research method uses quantitative statistics. The data analysis technique uses the classic assumption test. Hypothesis testing is assessed by multiple linear regression test, T test, and F test. The hypothesis test results of the determination coefficient obtained Adjusted R Square (R2) value of 58%, so it can be said that the variable Current Ratio (X1), Debt to Equity Ratio (X2), Working Capital Turnover (X3), and Total Assets Turnover (X4) affect the Return on Investment (Y) of 58% and the remaining 42% is influenced by other variables that are not found in this study.